MANFAAT KISAH ISLAM DALAM MENUMBUHKAN AKHLAK MULIA PADA DIRI SESEORANG - Mala, Jumaheroh Nur (Inspiratif Pendidikan, 2020)
The story is an attempt to direct and invite someone to think through feelings, so that life is carried out using a sense of love or encouraging humans to change behavior and renew their intentions to match demands, directions, conclusions, and lessons that can be learned from a story or story the. Meanwhile, morals themselves are something that occurs naturally in a person without being artificial. There are two kinds of morals, namely good morals or bad morals, good morals is an attitude that is preferred, while bad morals are an attitude that is hated by Allah, only oneself who are able to control and direct where you want to behave so that it is judged by God or society or vice versa if you do bad deeds that will be judged bad by God or humans.As for that there are a lot of benefits that can be taken from Islamic stories in growing the noble character of a person, such as strengthening and strengthening aqidah if what is studied in the story is the story of Islam, if what he learns are the stories of the Prophet then he gets priority because of the Prophet and Apostles are the chosen people of Allah, add insight in thinking, preserve history when stories that have been learned are conveyed to others, increase motivation in learning unknown stories, because usually when someone is interested in learning one science then he will continue to be interested in studying others, and if one who studies Islamic stories will avoid false stories.